ANALISIS BIAYA DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMPRODUKSI SENDIRI PADA RM. MINANG PUTRA - Nainggolan, Styven Farera; Ilat, Ventje; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
In this era of globalization the economy plays an important role so that competition in the business world is increasingly rapid. In running a business, the management system must be considered carefully in terms of accounting, finance, and decision making aspects. One of them is by making decisions about buying or producing their own raw materials needed to make a product. This study aims to analyze the differential costs in making or buying decisions on their own at RM. Minang Putra. This type of research is quantitative descriptive research that is a method that analyzes the problem by describing it on existing data, in the form of production cost calculation tables to determine the comparison of chicken meat production costs that can provide a clear description or description of the differential cost analysis in buying decision making or produce their own chicken meat at RM. Minang Putra. The results of the study show that the analysis of the differential cost and opportunity cost is very beneficial for RM. Minang Putra in decision making. And a better decision was taken by the RM. Minang Putra is self-producing because the costs incurred are more efficient when compared to buying chickens from outside.